A Review of Topogenous Peatland Management in Humbang Hasundutan Regency - Manalu, Sarah Patumona; Sabrina, T.; Delvian, Delvian (KnE Social Sciences, 2024)
Indonesia possesses a substantial expanse of peatland, including an area of over 265,500 square kilometers throughout the islands of Sumatra, Kalimantan, and Papua. Humbang Hasundutan Regency, located in North Sumatra, encompasses a total area of 2358 ha of peatland, making it a significant carbon reservoir worldwide. Peatlands within a district can be classified into two main types: topogenic and upland. This research aims to review issues related to peatlands in Humbang Hasundutan Regency and their sustainable management. The study was conducted using a systematic review method using e-books and journal articles to support a review that includes observational studies. E-books and journal articles were searched in online databases such as Google Scholar using the keywords: “Humbang Hasundutan,” “peatland,” and “topogenic.” The downloading process was done independently by the authors. This resulted in 5 e-books and 27 journal articles, 6 of which were observational or experimental studies conducted in the Humbang Hasundutan Regency while the rest discussed peatlands outside of Humbang Hasundutan Regency. Moreover, 20 articles discussed peatland management. This systematic review proves that many factors must be considered in good peatland management. These include the physiographic, topographical, and hydrological characteristics of the land, as well as fire prevention measures, the selection of appropriate materials and fertilizers, the use of geospatial technology, the adoption of adaptation strategies for peatland use, the way communities view peatlands, and the economic importance of peat ecosystems. Keywords: Humbang Hasundutan, peatland, topogenic